Tatars of the Grand Duchy of Lithuania in the United States of America - Siarhiej Miskiewicz (Lietuvos Istorijos Studijos)
At the end of the 19th and at the beginning of the 20th century, Tatars of the former Grand Duchy of Lithuania started migrating to new lands and countries including England, Argentina and America. They were looking for work and the USA became their preferred country. Many Tatars returned back to homeland, but most of them stayed in America and succeeded.